Blog-Based Learning Innovation with Powtoon Application in Facing Industrial Revolution 4.0 - T M Siregar; S Frisnoiry (Britain International for Academic Research (BIAR) Publisher, 2019)
The purpose of this research is to look at the feasibility of powtoon learning media on subjects by using blocks as learning resources, view responses to media using blocks on subjects, and see students' understanding ability after being given learning through powtoon media using blogs. The target of this research is lecturers and students who carry out learning with powtoon assistance at Medan State University. The method used to obtain the required information is to use the Google form questionnaire that is given online to lecturers and students and wants to see the understanding of students in using powtoon media. The results obtained from this study are Powtoon-assisted blog media in the Mathematics Learning Evaluation course declared valid with 88.2% included in the